How Should Donors Respond to Resource Windfalls in Poor Countries? From Aid to Insurance - Dobronogov, Anton; Gelb, Alan; Brant Saldanha, Fernando (World Bank, Washington, DC, 2014)
Natural resources are being discovered in more countries, both rich and poor. Many of the new and aspiring resource exporters are low-income countries that are still receiving substantial levels of foreign aid. Resource discoveries open up enormous opportunities, but also expose producing countries to huge trade and fiscal shocks from volatile commodity markets if their exports are highly concentrated. A large literature on the "resource curse" shows that these are damaging unless countries manage to cushion the effects through countercyclical policy. It also shows that the countries least likely to do so successfully are those with weaker institutions, and these are most likely to remain as clients of the aid system. This paper considers the question of how donors should respond to their clients' potential windfalls. It discusses several ways in which the focus and nature of foreign aid programs will need to change, including the level of financial assistance. The paper develops some ideas on how a donor like the International Development Association might structure its program of financial transfers to mitigate volatility. The paper outlines ways in which the International Development Association could use hedging instruments to vary disbursements while still working within a framework of country allocations that are not contingent on oil prices. Simulations suggest that the International Development Association could be structured to provide a larger degree of insurance if it is calibrated to hedge against large declines in resource prices. These suggestions are intended to complement other mechanisms, including self-insurance using Sovereign Wealth Funds (where possible) and the facilities of the International Monetary Fund.